DEVELOPMENT AND VALIDATION OF RAPID STABILITY-INDICATING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE DETERMINATION OF LINAGLIPTIN AND EMPAGLIFLOZIN IN PURE AND DOSAGE FORMS - EL SHEIKH, RAGAA; S HASSAN, WAFAA; YOUSSEF, EMANH; Y HAMDI, ABDULRAHMAN; AHMED BADAHDAH, NAIF; ESA ALZUHIRI, MUNEER; ELFETOUH GOUDA, AYMAN ABOU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A new, simple, rapid, sensitive, and accurate stability-indicating high-performance liquid chromatography (HPLC) method was developed and validated for the quantitative determination of linagliptin (LNG) and empagliflozin (EMP) in pure and tablet dosage forms. Methods: An isocratic HPLC method, using a C18 reversed-phase column (150 mm×4.6 mm i.d., particle size 5 μm) with an isocratic binary mobile phase consisting of phosphate buffer and acetonitrile (65:35, v/v), was investigated to separate the drug from its stress degradation products. The flow rate was 1.0 mL/min at ambient temperature and photodiode array detector is used at 226 nm for detection. The developed method was validated for system suitability, linearity, accuracy, precision, limits of detection and quantitation, specificity, stability, and robustness. Results: The retention time of LNG and EMP was found to be 3.276±0.002 and 6.966±0.0006 min, respectively. The calibration curve was found to be linear with the equation y=158926.39X+11.139, with a correlation coefficient of R2=0.9991 for LNG and y=22688.45X+4.259, with a correlation coefficient of R2=0.9994 for EMP over a concentration range of 2.5–7.5 μg/mL and 5.0–15 μg/mL for LNG and EMP, respectively. The limits of detection were 0.29 and 0.48 μg/mL for LNG and EMP, respectively, and the limits of quantification were 0.89 and 1.5 μg/mL for LNG and EMP, respectively. The recovery values of this method are 101.11% and 101.48% for LNG and EMP, respectively, and the reproducibility is within 0.070 and 0.277 for LNG and EMP, respectively. Conclusion: The proposed method is a rapid stability-indicating HPLC method that can be applied for the determination of LNG and EMP in pure and tablet dosage forms.